Hybrid Power for Energy Harvesting Design and Applied to Quadcopter System (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Quadcopter cannot fly for longer time even though the battery capacity is bigger. The suggested solution to this problem is to harvest energy from the surroundings and the system. This project is to study and designed a power system that uses surrounding energy to charge the battery of the quad-copter. The system requires a stable input charging to the battery from the harvester; a power controller is used to steady the input charging power. There are some limitations to the system where different harvester had different output power, which in turn difficult to choose a harvester to power the system. Thus, a hybrid power system is considered as a solution to generate a certain power from the harvester to the required system.